The Role of Human Capital in the Education Sector in Efforts to Create Reliable Organizational Human Resources - Suryono Efendi (International Journal of Science and Society, 2020)
Knowledge, skills and talents that may be utilized to provide professional services are human capital. The firm has a collective ability for the creation of ideas, innovations and appropriate solutions to help the company accomplish its business goals. The ability of human capital is for individuals to win the world's competition to offer employees with more financial value. Thus, this study is intended to establish the function of human capital in creating trustworthy human resources within the education sector. A qualitative technique is used in this study by gathering literature-based research data sources. The results demonstrate that the function of human capital is crucial in the education sector, since human capital provides a strong basis for the advancement of the educational world and for the creation of a new order that is essential in today's progressive world.